Kemampuan Spasial Mahasiswa Program Studi Tadris Matematika dalam Materi Geometri Transformasi - Ressy Rustanuarsi (J-PiMat : Jurnal Pendidikan Matematika, 2023)
Students' spatial ability plays an important role in understanding geometry concepts, especially Geometric Transformations. Therefore, it is necessary to know the students' spatial ability, so the lecturers can accommodate the learning needs of their students and provide an optimal learning. This study aimed to describe the initial spatial ability of students in Geometric Transformations material. This study was a descriptive study method with a quantitative approach. This study involved 28 students of Tadris Matematika IAIN Pontianak enrolled in fourth-semester and Geometric Transformations course of the 2022/2023 academic year. The data collecting instrument consisted of spatial ability test that measure three aspects of spatial ability, namely mental rotation, spatial orientation, and spatial visualization. The results of this study shows that the initial spatial ability of students in Geometric Transformations material are in the very high (10,7%), high (17,9%), medium (21,4%), low (35,7%), and very low (14,3%). The achievement of each of spatial ability indicator, namely mental rotation 53,57%, spatial orientation 40,71%, and spatial visualization 40,36%. In general, it can be concluded that students' initial spatial ability is in the medium category and all aspects of spatial ability need to be improved.